Does cohabiting with a partner affect stock market participation? - Camilla Skovbo Christensen; Isabel Skak Olufsen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2025)
Does the presence of a partner affect individuals' propensity to participate in the stock market? In this paper, we estimate the effect of cohabiting with a partner on stock market participation using rich administrative data from Denmark. It is a well-known puzzle that few people participate in the stock market, and existing literature has pointed to multiple barriers for an individual's participation decision. These barriers likely change when individuals cohabit with a partner. For example, cohabiting with a partner can influence expenses, risk, and financial information that all affect the participation decision. We show that cohabiting with a partner impacts financial decisions as cohabitation increases both entry into and exit from the stock market. Those who enter the stock market are predominantly individuals who cohabit with a partner with stock market experience. Those who exit are predominantly individuals who cohabit with a partner while also becoming homeowners. Thus, our results suggest that information spill-over within couples can increase participation, and that couples who purchase a home at cohabitation face other barriers such as liquidity needs and additional risk that offset the positive effects of cohabitation.
Keywords: D14; J12; G51; G53; 330; Household Finance; Stock Market Participation; Intra-Household Decision-Making